Penerapan Metode Ceramah dan Praktik sebagai Upaya Keberhasilan Proses Pembelajaran pada Mata Pelajaran PAI melalui Pengelolaan Kelas di SMK IPTEK Cilamaya Kabupaten Karawang - Mila Siti Hazizah; Hurul Aini; Mifa Rezkia Zanianti; Muhammad Miftah Fauzan (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2023)
This article was created based on the problems that occurred during the observations and interviews, namely regarding the application of the lecture method and practice as an effort to succeed in the learning process in PAI subjects through class management at SMK Science and Technology Cilamaya, Karawang Regency. The lecture and practice method is an approach used in learning to combine descriptive explanations from various sources, journals and books, as well as direct experience in the field. This research was conducted using a qualitative approach and data was collected through classroom observations, interviews with teachers and students, and documentation. The results of the study show that the application of the lecture and practice methods in PAI learning can increase student enthusiasm so that it can be said that classroom management in learning activities is successful. Keywords: class management, SMK IPTEK Cilamaya, islamic education